Tracing the Roots and Gateways of Radicalization in Countering Radicalism through a System Approach at the State Islamic University of Mataram - Nazar Naamy; Abdul Razak Abdulroya Panaemalae (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This paper examined counter-radicalization at UIN Mataram (Mataram State Islamic University) through a systematic approach. It focused on the forms, typology, roots, and gateways of radicalism in the Islamic university. This study categorized the roots of radicalism as the internal aspect of the system, while the gateways are referred to as the external component. The findings showed that the efforts to demolish radicalism at UIN Mataram should be preceded by an understanding of (a) the forms and typology of radicalism, (b) the roots and gateways of radical ideology, and (c) offering solutions through a systemic approach. These include leadership involvement, disseminating moderate Islamic values (washatiyyah), re examining the curriculum and materials prone to misunderstanding, modifying the pedagogical methods, involving Islamic boarding schools, and carrying out more studies on radicalism at Islamic higher education institutions.